Institutions, platforms and the production of debut success in contemporary book culture. Issue 1 (May 2023) - Parnell, Claire; Driscoll, Beth
Bestsellers, defined by the high sales numbers they achieve and the hype they generate, are success stories that periodically galvanise the contemporary book industry. Most publishers actively seek to produce bestsellers, using a range of strategies. Contemporary bestsellers, particularly from peripheral markets and by debut authors, are produced through the strategic joining of two co-existing modes of capitalism: conglomerate capitalism and platform capitalism. This article analyses the publication pathways and reception of two debut bestsellers by Australian authors: Hannah Kent's Burial Rites and Heather Morris' The Tattooist of Auschwitz . To analyse these case study titles, we constructed publishing histories, collected five media reviews for each book from reputable publications and literary journals, and scraped the top 100 reviews on Goodreads. These case studies show how the particular textual qualities of each book, highlighted in publishers' marketing material, shape the media and reader reception of each book, and the mechanisms and strategic alliances with traditional institutional and platform networks at work in producing success in post-digital book culture. Bestsellers show the logics and systems of an industry in flux, and the strategies that can support a debut work to reach a mass audience.